Analisis Rasio Permodalan, Likuiditas, Rentabilitas, Kualitas Aktiva Produktif dan NPF di KSPPS BTM Surya Umbulharjo Yogyakarta (Analysis of Capital Ratio, Liquidity, Profitability and NPF at KSPPS BTM Surya Umbulharjo Yogyakarta) - Adha, Mufti Alam; Wahyudi, Rofiul (Universitas Muhammadiyah Sidoarjo, 2020)
The main objective of this research is to analyze the ratio analysis of capital, liquidity, profitability, and non-performing financing (NPF) at KSPPS BTM Surya Umbulharjo Yogyakarta. This research is quantitative with a descriptive approach. Source of research data derived from primary and secondary documentation Annual Members Meeting (RAT). The research data analysis technique used is descriptive statistical analysis. This approach is used to provide an overview of the financial performance of KSPPS BTM Surya Umbulharjo Yogyakarta. The results showed that the BTM capital ratio during the study period showed a healthy category, the liquidity ratio was in the liquid category, the profitability ratio showed in the low category, and the NPF ratio showed in the sufficient category.